National parks best practices: Lessons from a century's worth of national parks management - Kalifi Ferretti-Gallon; Emma Griggs; Anil Shrestha; Guangyu Wang (International Journal of Geoheritage and Parks, 2021)
While the importance of ecological conservation and encouraging public recreation in national parks is widely recognized, challenges to achieving these goals persist. With over a century of national park management experience, the institutional knowledge of national park systems in Australia, Canada, New Zealand, and the United States can offer a valuable insight into management best practices. Twelve open-ended semistructured interviews with national park experts representing the four systems revealed valuable lessons learned in major facets of national park management. Overall, our results suggest that effective and sustainable national park management requires federally-based organizational framework with deference to local institutions at park-level, stakeholder inclusion in park management decision-making, public engagement encouraged by information-sharing and education, clarity on boundaries to improve relations with adjacent land owners, and prioritizing improved indigenous relations. Interviews highlighted that better park governance is rooted in education to raise awareness of the importance of national parks and park systems to the public. Tourism and climate change were widely anticipated to increasingly pose challenges to park management, underscoring a shared urgency to address these issues.